The role of religious mentoring in countering extremism and terrorism - L.M. Ravandi-Fadai (Ученые записки Казанского университета: Серия Гуманитарные науки)
Religious, Islamic in particular, extremism under the current political conditions on a global scale has been discussed. A significant obstacle to stopping the alarming rise in young people taking up arms on behalf of various terrorist organizations is the lack of charismatic spiritual leaders promoting a peaceful and traditional understanding of Islam, especially in regions of unrest. The paper focuses on the important role that religious mentoring can play against extremism and terrorism, specifically the institution of Marja al-taqlid, and provides an overview of the particular forms of Islamic extremism that have emerged today. The results of our analysis suggest that extremism can be fought only through collective action of national, social, and religious institutions.